2020
DOI: 10.1002/pon.5265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fear of cancer recurrence on survival among lymphoma patients

Abstract: Objective: This study aimed to evaluate fear of cancer recurrence (FCR) among lymphoma patients who completed treatment and its impact on survival and quality of life (QOL). Methods: In this prospective cohort study, 467 lymphoma patients were included who completed treatment with curative intent between February 2012 and March 2017. FCR was measured using a question from the Korean version of the QOL in Cancer Survivors Questionnaire. QOL and general health and functioning were measured using the European Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…24 Severe FCR has a negative impact on survival in the lymphoma population. 25 The present study highlighted the differential need of the myeloma population and provided a wealth of data to inform the planning and implementation of targeted interventions.…”
Section: Discussionmentioning
confidence: 85%
“…24 Severe FCR has a negative impact on survival in the lymphoma population. 25 The present study highlighted the differential need of the myeloma population and provided a wealth of data to inform the planning and implementation of targeted interventions.…”
Section: Discussionmentioning
confidence: 85%
“…Under the outbreak of COVID‐19, psychosocial clinicians were restricted from the clinics, oncologists became the main personnel providing varied psychological interventions to cancer patients. Poor recognition of depression and anxiety was shown to be associated with impaired survival in cancer patients 8,9 . And cancer patients receiving early psychological interventions had less aggressive care at the end of life and longer survival 10 .…”
Section: Discussionmentioning
confidence: 99%
“…45 Physicians can also help moderate patients' anxiety, use telemedicine to examine anxiety and fear of relapse, and provide appropriate psychological referrals. 46 Studies have shown that depression and anxiety are associated with impaired survival in cancer patients 47,48 and early psychological interventions in cancer patients can lead to longer survival. 49 The results of the present study did not show a significant relationship between CDAS and mindfulness.…”
Section: Discussionmentioning
confidence: 99%